2013
DOI: 10.1158/0008-5472.can-12-2101
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Folate Receptors to Treat Invasive Urinary Bladder Cancer

Abstract: Folate receptors (FR) may be of use for targeted delivery of cytotoxic drugs in invasive urothelial carcinoma (iUC), for which improved therapy is needed. FR expression and function in iUC were explored and the antitumor activity and toxicity of a folate-targeted vinblastine conjugate were evaluated in dogs with naturally occurring iUC, an excellent model for human iUC. FR immunohistochemistry was carried out on iUC and normal human and dog bladder tissues together with nuclear scintigraphy in dogs to monitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…Epofolate (BMS-753493), a folic acidepothilone conjugate, completed Phase I and Phase II assessments for the treatment of advanced solid tumours but, owing to lack of efficacy, has been withdrawn from further clinical investigation 168,169 . A considerably more potent folate-tubulysin conjugate, EC1456, entered clinical trials this year (NCT01999738), and EC0905, a folate-vinblastine conjugate, has shown considerable promise in preclinical studies for treating spontaneous bladder cancers in dogs 170 .…”
Section: Mip-1072mentioning
confidence: 99%
“…Epofolate (BMS-753493), a folic acidepothilone conjugate, completed Phase I and Phase II assessments for the treatment of advanced solid tumours but, owing to lack of efficacy, has been withdrawn from further clinical investigation 168,169 . A considerably more potent folate-tubulysin conjugate, EC1456, entered clinical trials this year (NCT01999738), and EC0905, a folate-vinblastine conjugate, has shown considerable promise in preclinical studies for treating spontaneous bladder cancers in dogs 170 .…”
Section: Mip-1072mentioning
confidence: 99%
“…As such, it has been considered as target in several therapeutic strategies. [26][27][28][29][30][31][32][33] The bidirectional RFC, which is ubiquitously expressed in mammalian cells and reported to be overexpressed in cancer, is also an important uptake mechanism of folate and antifolates. [34][35][36][37][38][39][40][41] An impairment of RFC synthesis or mutations in the RFC protein can lead to cellular dysfunctions and therefore to resistances against chemotherapeutic drugs like MTX.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of bladder cancer cases are superficial in the early stage, and 70% of such patients suffer relapse following surgery, with 30% of relapses developed towards the later stages of the disease (1). In addition, 15-30% of cases are invasive at the early stage, even if therapy is received for early metastasis (22). The prognosis of patients with urothelial bladder carcinoma is determined by the depth of invasion, metastasis and recurrence.…”
Section: Discussionmentioning
confidence: 99%